PERTANGGUNGJAWABAN PIDANA PENYIDIK POLRI ATAS TINDAKAN ABUSE OF POWER DAN PERLINDUNGAN HUKUM BAGI KORBANNYA - Agnes Putri Adianto; Michael Gondowidjaja (Law Department, University of Widya Gama Mahakam Samarinda, 2023)
Background: Indonesia is one that upholds fair and certain law enforcement. However, sometimes these two things do not materialize properly and optimally because there are still arbitrary law enforcement actions by law enforcement officials, especially police investigators. The actions taken can be referred to as abuse of power. The potential for abuse of power arises when police investigators have other goals to benefit themselves, other people or certain groups through law enforcement. Abuse of power can cause harm to victims, both materially and immaterially. National Police investigators who abuse power can be criminally prosecuted if they commit an act that has elements of a crime. It is mandatory for the National Police investigators to be held criminally liability. In addition, victims of abuse of power also have the right to receive legal protection. Research Method: The research method uses a normative juridical approach Findings: The respect for law enforcement that is fair and definite obliges every police investigator to carry out his duties and authorities in accordance with statutory regulations and if he violates the law by committing an abuse of power, the personnel must be held accountable, including criminal liability. Conclusion: Victims of abuse of power are entitled to legal protection for losses arising from abuse of power